2019
DOI: 10.1016/j.gca.2019.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Nebular history of an ultrarefractory phase bearing CAI from a reduced type CV chondrite

Abstract: Ultrarefractory (UR) phases in calcium-aluminum-rich inclusions (CAIs) could have formed at higher temperature compared to common CAI minerals and thus they potentially provide constraints on very high temperature processes in the solar nebula. We report a detailed characterization of the mineralogy, petrology and oxygen isotopic composition of an UR phase davisite (CaScAlSiO 6 ) bearing CAI from a reduced type CV chondrite. The CAI is an irregular-shaped, compound inclusion that consists of five units that ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 127 publications
(223 reference statements)
0
1
0
Order By: Relevance
“…Most pristine CAIs in most unmetamorphosed carbonaceous chondrites are usually uniformly 16 O-rich (D 17 O~-22&; Yurimoto Krot et al 2012) and should have formed in the 16 O-rich gaseous reservoirs (Yurimoto et al 2008). Meanwhile, numerous investigations suggested that 16 Opoor gaseous reservoirs might also exist in the CAI formation regions (Yurimoto et al 1998;Simon et al 2011;Katayama et al 2012;Kawasaki et al 2012Kawasaki et al , 2017Park et al 2012;Zhang et al 2015;Yoshizaki et al 2019;Krot et al 2019aKrot et al , 2019b. The presence of 16 Opoor gaseous reservoirs might have led to the formation of uniformly 16 O-poor CAIs and CAIs with heterogeneous oxygen isotopic compositions.…”
Section: Oxygen Isotopic Heterogeneity In Cai 007mentioning
confidence: 99%
“…Most pristine CAIs in most unmetamorphosed carbonaceous chondrites are usually uniformly 16 O-rich (D 17 O~-22&; Yurimoto Krot et al 2012) and should have formed in the 16 O-rich gaseous reservoirs (Yurimoto et al 2008). Meanwhile, numerous investigations suggested that 16 Opoor gaseous reservoirs might also exist in the CAI formation regions (Yurimoto et al 1998;Simon et al 2011;Katayama et al 2012;Kawasaki et al 2012Kawasaki et al , 2017Park et al 2012;Zhang et al 2015;Yoshizaki et al 2019;Krot et al 2019aKrot et al , 2019b. The presence of 16 Opoor gaseous reservoirs might have led to the formation of uniformly 16 O-poor CAIs and CAIs with heterogeneous oxygen isotopic compositions.…”
Section: Oxygen Isotopic Heterogeneity In Cai 007mentioning
confidence: 99%